KAJIAN KESEHATAN LINGKUNGAN PERKOTAAN MENURUT ASPEK DAYA DUKUNG KAWASAN JALUR HIJAU JALAN DALAM PENGENDALIAN CEMARAN GAS BUANG KENDARAAN BERMOTOR DI KOTA RAHA - Fajar Sukma Jaya; Hasddin Hasddin (Yayasan Akrab Pekanbaru, 2019)
The results of the study show that; 1) The air quality in Kota Raha according to the concentration of carbon monoxide (CO) ranges from 65.89-131.63 µg/m3, which is still below the ambient air quality standard according to the provisions of Government Regulation (PP) No.41 of 1999, which is permitted that is 30,000 µg/m3. The value of the Hydrocarbon (HC) concentration is in the range of 20.84-37.11 µg/m3, still below the ambient air quality standard according to RI PP No.41 of 1999 which is permissible at 160 µg / Nm3. Values ​​from the concentration of Nitrogen Oxide (NOx) ranged from 4.28-13.84 µg/m3, still below the ambient air quality quality standard, according to Republic of Indonesia Regulation No.41 of 1999 which is permissible at 400 µg/m3, and SOx concentrations ranged from 0.15-0.51 µg/m3, still below the air quality book according to RI Regulation No.41 of 1999 which allowed 900 µg/m3; (2) The current green road RTH in Raha City is 2.95 ha with carbon absorption capacity of 920.06 tons/year while Raha City produces emissions resulting in an emission load of 1,328,701 tons/year, meaning that there is around 408.64 tons/year remaining emissions not absorbed. Thus, green road RTH on the existing road has not been able to control or absorb gas from motor vehicle exhaust gases; and (3) The direction for controlling motor vehicle exhaust emissions based on the carrying capacity of the green lane in Kota Raha is to do extensive addition of RTH needs especially in reducing CO and HC by 28,024 m2 or 2,80 ha or about 30.75% of the total available RTH.